D–A systems based on oxazolone–coumarin triazoles as solid-state emitters and inhibitors of human cervical cancer cells (HeLa). (7th December 2021) - Shamsiya, Aranhikkal; Bahulayan, Damodaran
Abstract : D–A systems with solid-state emission and anticancer properties have been synthesized in three steps via the MCR-Click protocol. Abstract : A collection of solid-state emitters based on oxazolone–coumarin triazoles with the potential to induce apoptosis in the human cervical cancer cell line HeLa is reported. These new classes of fluorescent inhibitors were synthesized by the sequential use of multicomponent reactions (MCR) and click chemistry with oxazolone alkynes and coumarin azides and the origin of their solid state emission properties were related to an unconventional AIE process. The significantly high first-order hyperpolarizability values (36–118 times higher than the standard molecule urea) obtained from the DFT calculations showed that the emission from these molecules follows nonlinear optical characteristics. The molecules also showed excellent binding affinity towards CDK2 with high docking scores and the binding sites obtained from docking studies are in good agreement with the reactivity sites determined from the DFT-based molecular electrostatic potential (MEP) analysis. Cytotoxicity studies of the selected molecules showed the potential of these molecules as inhibitors of human cervical cancer cells (HeLa). Overall, the optical and biological properties of these new solid-state emitters are promising for a broad spectrum of applications in medicinal and materials chemistry.